An inquiry into the practice of cultural creativity in libraries of China - Pan Xin, (IJRDO- Journal of Educational Research, 2019)
The cultural and creative industry is the most dynamic, promising and value-added industry and the Chinese government attaches great importance to it. Libraries at all levels begin to actively explore and try to carry out cultural and creative practice. The practice of cultural creativity in libraries can creatively transform the cultural resources of library collections and expand their cultural functions. There are two modes for libraries to carry out cultural and creative practice : industrial development type and industrial development service. Libraries should start with regional characteristics and collection characteristics, and carry out cultural and creative practice with professional help and modern science and technology.